Usefulness of the Nonself-Self Algorithm of HLA Epitope Immunogenicity in the Specificity Analysis of Monospecific Antibodies Induced during Pregnancy - Duquesnoy, Rene J.; Marrari, Marilyn; Mulder, Arend (Frontiers in immunology, 2015)
HLAMatchmaker is a program to analyze the epitope specificities of HLA antibodies. It considers each HLA allele as a string of eplets. Intralocus and interlocus comparisons between donor and recipient alleles offer a structural assessment of compatibility and an analysis of allele panel reactivity patterns can generate information about epitope specificities of HLA antibodies. However, HLAMatchmaker cannot always generate conclusive interpretations of reactivity patterns of all monospecific antibodies, which by definition recognize single epitopes. We have therefore developed a new antibody analysis approach that utilizes the nonself-self algorithm of HLA epitope immunogenicity. It is based on the concept that HLA antibodies originate from B-cells with immunoglobulin receptors to self-HLA epitopes on one given allele and which can be activated by epitopes defined by a few nonself residue differences whereas the remainder of the structural epitope of the immunizing allele consists of self residues. Three human monoclonal class I antibodies from HLA typed women sensitized during pregnancy were tested in Ig-binding assays with single alleles on a Luminex platform. Three new HLA epitopes were identified; they are defined by combinations of nonself- and self-residues for one allele of the antibody producer. The nonself-self paradigm of HLA epitope immunogenicity offers a second approach to analyze HLA antibody specificities.